CORAK DAN METODOLOGI TAFSIR INDONESIA â€œWAWASAN AL-QUR`ANâ€ KARYA M. QURAISH SHIHAB - Ali Aljufri (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2015)
This paper introduces the reader regarding the Indonesia interpretation. The work in question was Wawasan Al-Qur`an by Quraish Shihab. In introducing this work the author describes the style of interpretation, interpretation methods and techniques of writing. The author also discusses the figure of Quraish Shihab in briefly description. In addition, he also explained about the interpreter`s method in explaining the themes contained in the work of Wawasan Al-Qur`an . In reviewing the work of Wawasan Al-Qur`an author tried to express all aspects discussed in the work, so it will be seen what method is used by Quraish Shihab in interpreting the verses of the Koran.